E-therapy in the treatment and prevention of eating disorders: A systematic review and meta-analysis. - Loucas, C; Fairburn, C; Whittington, C; Pennant, M; Stockton, S; Kendall, T (Elsevier, 2014)
The widespread availability of the Internet and mobile-device applications (apps) is changing the treatment of mental health problems. The aim of the present study was to review the research on the effectiveness of e-therapy for eating disorders, using the methodology employed by the UK's National Institute for Health and Care Excellence (NICE). Electronic databases were searched for published randomised controlled trials of e-therapies, designed to prevent or treat any eating disorder in all age groups. Studies were meta-analysed where possible, and effect sizes with confidence intervals were calculated. The GRADE approach was used to determine the confidence in the effect estimates. Twenty trials met the inclusion criteria. For prevention, a CBT-based e-intervention was associated with small reductions in eating disorder psychopathology, weight concern and drive for thinness, with moderate confidence in the effect estimates. For treatment and relapse prevention, various e-therapies showed some beneficial effects, but for most outcomes, evidence came from single studies and confidence in the effect estimates was low. Overall, although some positive findings were identified, the value of e-therapy for eating disorders must be viewed as uncertain. Further research, with improved methods, is needed to establish the effectiveness of e-therapy for people with eating disorders.